1999
DOI: 10.1680/macr.1999.51.6.397
|View full text |Cite
|
Sign up to set email alerts
|

Towards the design of reinforced concrete eccentric beam—column joints

Abstract: The authors have previously proposed a simplified method for the design of external beam±column joints. This paper extends that work to joints in which one of the beams is eccentric to the column. Such connections occur in practice owing to architectural and geometrical constraints. Results are presented for tests on ten specimens in which one of the two beams framing into the column was eccentric to the column. The authors are unaware of any previous tests on such specimens. The tests were designed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…A previous analysis 5,8 of all known test data 6,7,9±17 showed that joint shear strength (a) is sensibly independent of column axial load unless a hinge forms in the upper column (b) is proportional to p f 9 c for joints without stirrups (c) reduces with increasing joint aspect ratio h b ah c . Test data are limited (see Fig.…”
Section: Strut and Tie Model For Beam±column Joint Without Stirrupsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous analysis 5,8 of all known test data 6,7,9±17 showed that joint shear strength (a) is sensibly independent of column axial load unless a hinge forms in the upper column (b) is proportional to p f 9 c for joints without stirrups (c) reduces with increasing joint aspect ratio h b ah c . Test data are limited (see Fig.…”
Section: Strut and Tie Model For Beam±column Joint Without Stirrupsmentioning
confidence: 99%
“…The first author has carried out an extensive survey 5,8 of test data 6,7,9±13 to determine the influence of stirrups on joint shear strength. Joint stirrups were found to be effective if placed between the underside of the main reinforcement and the top of the compressive stress block in the beam (assumed to be of depth 0 X 375h b ).…”
Section: Strut and Tie Model For Beam±column Joints With Stirrupsmentioning
confidence: 99%
See 3 more Smart Citations